BOOK REVIEW VIOLENCE AGAINST WOMEN. REALITIES, CHALLENGES AND ACTORS IN THE IMPLEMENTATION OF THE NATIONAL LAW 26485 IN LA PAMPA BY DANIELA M. J. ZAIKOSKI BISCAY AND BETSABÉPOLICASTRO (COMPILERS) 2 EDUNLPAM, 2017 (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
BOOK REVIEW: Violence against women. Realities, challenges and actors in the implementation of the National Law 26485 in La Pampa by Daniela M. J. Zaikoski Biscay and BetsabéPolicastro (compilers) 2 EdUNLPam, 2017
Keywords: women; state; judiciary; discourse; patriarchy